Inﬂuence of the Organo-Mineral Fertilization on the Lettuce Growth (Lactuca Sativa L.) in the Gardening Site of Houeyiho (Benin) - ADJAKPA, Boco Jacques; AHOTON, ESSÈHOU LÉONARD; CHIDIKOFAN, Floriane; AKPO, Léonard Elie (My University, 2012)
Fertilizers are products which are rich in mineral elements necessary to the growth and the harmonious development of cultivation. For that, a study on Lactua sativa L. fertilization (organic and mineral fertilizer) was undertaken in order to identify the best fertilizer adapted to Houéyiho site in Cotonou. The methodology adopted is based on agronomic trial using a complete randomly block with three treatments and three repetitions: organic fertilizer (OF), mineral fertilizer (MF) and no fertilizer (NF). Observations are made on the number of leaves, the cut diameter and the plant height. The results of this work show that all the three treatments have guaranteed a good growth of plants. Generally speaking, the treatment organic fertilizer has promoted the best growth and the best development of the plant. With regard to the two others treatments, mineral fertilizer and no fertilizer, the growth and the development are the same. This is due because the soil is rich in mineral fertilizer. Organic fertilizer, because its high level in organic matter, has improved the soil structure by promoting taking root of culture and its good feeding and growth. Some references have been given on the fertilizer type which will be used to cultures in the future.
Keywords: lettuce; compost; mineral fertilizer; yield; Benin